Impact of Intellectual Capital in Healthcare Tourism Industry in Pakistan - Khushbakht, Hina; Muhammad Tahir, Ali Shah; Muhammad, Khalique (2020)
The objective of this research is to determine the impact of intellectual capital on innovation in healthcare tourism industry in Islamabad Pakistan. Healthcare tourism industry plays a significant contribution in the development and growth of the Pakistan economy. The components of intellectual capital were drived from the Intergrated Intellectual Capital Model (IICM). A total number of 190 respondents were participated in this study. Purposive sampling techniques was used to selcted the respondnets. The data were analy through Statistical Package for Social Sciences (SPSS). The findings of this study showed that four out of six proposed hypotheses were accepted. The empirical findings of this study will be useful for the managers and policy makers to enhance innovation in their organizations.